Comparative Proteomic Analysis of the Effect of Periplocoside P from Periploca sepium on Brush Border Membrane Vesicles in Midgut Epithelium of Mythimna separata Larvae - Mingxing Feng; Yankai Li; Xueting Chen; Quansheng Wei; Wenjun Wu; Zhaonong Hu (Toxins, 2017)
Periplocoside P (PSP), a novel compound isolated from Periploca sepium Bunge, possesses insecticidal activity against some lepidopterans, such as Mythimna separata. In M. separata, the brush border membrane vesicles of the midgut epithelium are the initial site of action of periplocosides. We conducted two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time of flight/time of flight mass spectrometry analysis to analyze differentially expressed proteins (DEPs) from periplocoside P (PSP)-treated M. separata. We successfully isolated seven up-regulated and three down-regulated DEPs that have been previously identified, as well as a novel DEP. The DEPs are implicated in protein degradation, transporter, folding, and synthesis, and in juvenile hormone biosynthesis. DEPs involved in the oxidative phosphorylation energy metabolism pathway are enriched. Through real-time polymerase chain reaction assay, we confirmed that vma1 expression is significantly up-regulated expression levels in PSP-treated M. separata larvae. Enzymology validation further indicated that PSP can significantly inhibit V-type ATPase activity in a concentration-dependent manner. Given these results, we speculate that in M. separata, the V-type ATPase A subunit in the midgut epithelium is the putative target binding site of periplocosides. This finding provides preliminary evidence for the mode of action of periplocosides.